Speed curve analysis-based determination of additional resistance to train motion from undercarriage generators - I. O. Lobytsin; I. A. Pankov; V. V. Fedin; N. A. Baranov; K. I. Shvedin; S. O. Litvintsev (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. Traction calculations take into account additional resistance to train motion from the action of undercarriage generators using statistical data from field tests of rolling stock samples. Comparative analysis of calculated and actual results shows system deviations with real fuel and energy consumption exceeding the calculated values.Materials and methods. The analysis and detailing involved data of the memory block of the electric locomotives microprocessor control and diagnostic system, transcripts of the integrated train safety system and locomotive technical radio communication system. The authors applied methods of data array approximation and extrapolation, numerical integration, statistical data processing, and the method of energy-optimal traction calculation.Results. Traction calculation of the influence of undercarriage generators on resistance to movement shows that fuel and energy consumption exceeds the consumption without the influence of generators by 15% in average. The researchers found that the intensity of electrical equipment use in passenger cars has a variable effect on the performance of undercarriage generators. Most notably, the research prompted a new way of determining the resistance to motion from undercarriage generators.Discussion and conclusion. This method of estimating the additional resistance to train motion from undercarriage generators can be scaled to various train movement problems solved with statistical data using mathematical models. The algorithm developed by the authors would find its application in the systems of calculation, analysis and planning of fuel and energy resources consumption.